2022
DOI: 10.1111/jzo.12981
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐relationships among body mass, body dimensions, jaw musculature and bite force in reptiles

Abstract: Bite force is important in understanding how feeding biomechanics impacts the life-history of vertebrates. Bite force has been measured in many lizards and crocodilians but fewer turtles and snakes. Few comparative interspecific studies exist of the inter-relationships between body size, jaw musculature and bite force. This study collated data reported in the literature for bite force and mass of the jaw musculature in reptiles and explored the relationships between these variables and body mass and size. Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…The parrots varied in the relative composition of the muscle in the jaw apparatus with genera varying in their arrangement of the adductor and protractor muscles. Unlike lizards, whose head size scales isometrically with body mass (Deeming 2022), as Psittaciformes get larger, their heads become a proportionally larger part of their body. The jaw muscles, however, scaled isometrically with the size of these proportionally larger heads.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The parrots varied in the relative composition of the muscle in the jaw apparatus with genera varying in their arrangement of the adductor and protractor muscles. Unlike lizards, whose head size scales isometrically with body mass (Deeming 2022), as Psittaciformes get larger, their heads become a proportionally larger part of their body. The jaw muscles, however, scaled isometrically with the size of these proportionally larger heads.…”
Section: Discussionmentioning
confidence: 97%
“…This study, therefore, explored allometry in the different jaw muscle masses from a variety of parrot species ranging in body mass by 40-fold. Given the similarity in skull and beak morphology seen in the Psittaciformes (Zusi 1993), because earlier studies in reptiles showed that muscle mass isometrically scaled with body mass and showed marginal positive allometry with skull size (Deeming 2022), we hypothesized that this would also be true in Psittaciformes. The results will provide an insight into how body size impacts on the myology of the jaw apparatus in this order and how this may impact on the functional properties of the jaw apparatus, i.e.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In sharp contrast to the magnitude of bite force, the positive static allometry appears to be less remarkable: around 70% of available intraspecific studies reported significant positive allometry of bite forces, if often less pronounced [including one study that also reported negative allometry for other phenotypes of the same species, 100]). Remarkably, and with the notable exception of bats and finches [89, 108111], bite force studies involving different genera typically report isometric scaling [89, 112, 113, and see meta-analysis above], or even modest negative allometry [85, 103, 114117]. There thus appears to be a systematic difference between ontogenetic, static and evolutionary scaling of bite forces.…”
Section: Discussionmentioning
confidence: 99%